Quantifying the effects of species traits on predation risk in nature: A comparative study of butterfly wing damage. Issue 3 (4th December 2019) - Molleman, Freerk; Javoiš, Juhan; Davis, Robert B.; Whitaker, Melissa R. L.; Tammaru, Toomas; Prinzing, Andreas; Õunap, Erki; Wahlberg, Niklas; Kodandaramaiah, Ullasa; Aduse‐Poku, Kwaku; Kaasik, Ants; Carey, James R.
Abstract: Evading predators is a fundamental aspect of the ecology and evolution of all prey animals. In studying the influence of prey traits on predation risk, previous researchers have shown that crypsis reduces attack rates on resting prey, predation risk increases with increased prey activity, and rapid locomotion reduces attack rates and increases chances of surviving predator attacks. However, evidence for these conclusions is nearly always based on observations of selected species under artificial conditions. In nature, it remains unclear how defensive traits such as crypsis, activity levels and speed influence realized predation risk across species in a community. Whereas direct observations of predator–prey interactions in nature are rare, insight can be gained by quantifying bodily damage caused by failed predator attacks. We quantified how butterfly species traits affect predation risk in nature by determining how defensive traits correlate with wing damage caused by failed predation attempts, thereby providing the first robust multi‐species comparative analysis of predator‐induced bodily damage in wild animals. For 34 species of fruit‐feeding butterflies in an African forest, we recorded wing damage and quantified crypsis, activity levels and flight speed. We then tested for correlations between damage parameters and species traits using comparative methods that account for measurement error. We detected considerable differences in the extent, location and symmetry of wing surface loss among species, with smaller differences between sexes. We found that males (but not females) of species that flew faster had substantially less wing surface loss. However, we found no correlation between cryptic coloration and symmetrical wing surface loss across species. In species in which males appeared to be more active than females, males had a lower proportion of symmetrical wing surface loss than females. Our results provide evidence that activity greatly influences the probability of attacks and that flying rapidly is effective for escaping pursuing predators in the wild, but we did not find evidence that cryptic species are less likely to be attacked while at rest. Abstract : Among 35 species of fruit‐feeding butterflies in an African forest, species that can fly faster have less wing surface loss that is more biased to hindwings, suggesting that flying rapidly is effective for escaping pursuing birds in the wild, sometimes with hindwing damage.